PEMBUATAN BIOETANOL DARI BATANG KELAPA SAWIT (Elais Guineensis Jacq.) MELALUI PROSES PRETREATMENT MENGGUNAKAN H2SO4 DAN FERMENTASI MENGGUNAKAN RAGI ROTI (Saccharomyces cerevisiae) - Giyanto; Saragih, Sri Wahyuna; Rahimah (Institut Teknologi Sawit Indonesia (ITSI), 2023)
Unproductive oil palm stems can produce Umbut which is the raw material for bioethanol production. In general, the production process of bioethanol from lignocellulosic materials includes oil palm stalks. The bioethanol production process goes through several stages of physical, chemical or biological pretreatment, polymer saccharification, sugar fermentation, and ethanol separation and purification. This study aims to determine the production of bioethanol from oil palm stems (Elaeis Guineensis Jacq) through a pretreatment process using H2S04 and fermentation using baker's yeast (Saccharomyces cerevisiae). The method used in this study was a Completely Randomized Design (CRD) Non Factorial with 3 treatment levels and 1 control, and 3 repetitions (Triplo) with a total sample of 12 samples. The resulting bioethanol is then tested (moisture content, yield, and pH). The resulting data were analyzed using ANOVA and Duncan's test. Based on the results of this study, the best treatment was found in the H0 treatment with a yield of 34.5%, 1.52% moisture content and 5,6 % pH